Relationships between walking speed, activities and participation in people with chronic stroke in Burundi - Félix Nindorera; Ildephonse Nduwimana; Alexis Sinzakaraye; Yannick Bleyenheuft; Jean-Louis Thonnard; Oyéné Kossi (AOSIS, 2022)
Background: Reduced walking speed because of a stroke may limit activities of daily living (ADLs) and restrict social participation. Objectives: To describe the level of balance impairment, activity limitations, and participation restrictions and to investigate their relationship with walking speed in Burundians with chronic stroke. Methods: This cross-sectional study involved adult stroke survivors. Walking speed, balance, ADLs and social participation were assessed with the 10-meter walk test (10 mWT), the Berg balance scale (BBS), the activity limitation stroke scale and the participation measurement scale, respectively. In order to determine ambulatory independence status, participants were stratified into three walking speed groups (household ambulation, limited ambulation and full-community ambulation), based on the Perry classification. Results: Fifty-eight adults (mean age 52.1 ± 11.4 years) with chronic stroke were included in our study. Most participants had severe balance impairments (median BBS score, 27). Their mean (± standard deviation [SD]) walking speeds, ADL levels and social participation levels were 0.68 ± 0.34 m/s, 50.8% ± 9.3% and 52.8% ± 8.6%, respectively. Walking speed correlated moderately with balance (rho = 0.5, p  0.001) and strongly with ADL level (r = 0.7, p  0.001) but not with participation level (r = 0.2, p = 0.25). Conclusion: Using socio-culturally suitable tools, our study showed that walking speed correlates robustly with balance and ADL ability, but not with social participation, in Burundi, a low-income country. Clinical implications: Exercises targeting walking speed would be very useful for people with chronic stroke living in low-resource countries, in order to promote their functional independence.